Chromosomal integration of the Klebsiella pneumoniae carbapenemase gene (blaKPC) in Klebsiella species: Elusive but not rare - Mathers, A; Stoesser, N; Chai, W; Carroll, J; Barry, K; Cheruvanky, A; Sebra, R; Kasarkis, A; Peto, T; Walker, A; Sifri, C; Crook, D; et al. (American Society for Microbiology, 2016)
Carbapenemase genes in Enterobacteriaceae are mostly described as being plasmid-associated. However, the genetic context of carbapenemase genes is not always confirmed in epidemiological surveys, and the frequency of their chromosomal integration is therefore unknown. A previously sequenced collection of blaKPC-positive Enterobacteriaceae from a single US institution (2007-2012; n=281 isolates, 182 patients) was analyzed to identify chromosomal insertions of Tn4401, the transposon most frequently harboring blaKPC. Using a combination of short- and long-read sequencing, we confirmed five independent chromosomal integration events from 6/182 (3%) patients, corresponding to 15/281 (5%) isolates. Three patients had isolates identified by peri-rectal screening and three had infections which were all successfully treated. When a single copy of blaKPC was in the chromosome one or both of the phenotypic carbapenemase tests were negative. All chromosomally integrated blaKPC were from Klebsiella spp., predominantly K. pneumoniae clonal group (CG)258, even though these represented only a small proportion of the isolates. Integration occurred via IS15-ΔI mediated transposition of a larger, composite region encompassing Tn4401 at one locus of chromosomal integration, seen in the same strain (K. pneumoniae ST340) in two patients. In summary, we identified five independent chromosomal integrations of blaKPC in a large outbreak, demonstrating that this is not a rare event. blaKPC was more frequently integrated into the chromosome of epidemic CG258 K. pneumoniae lineages (ST11, ST258, ST340), and was more difficult to detect by routine phenotypic methods in this context. The presence of chromosomally integrated blaKPC within successful, globally disseminated K. pneumoniae strains is therefore likely underestimated.